An Analysis of Grammatical Errors in Speech Joko Widodo, Presidential of Indonesia, at APEC CEO Summit ‘’YouTube Video by APEC’’ - Elperinda Silaen; Jelly Hutagaol; Nurma Dhona Handayani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2022)
Language is a means of communication for every human being. Also, several types of languages ​​such as regional languages, state languages ​​and international languages ​​is English. English in general has existed since elementary school to college. Many adults are still wrong in the use of good and correct English so that it requires more extra learning. One method of improving English through vocabulary is speaking like a speech. In the speech, in this study, researchers took sources from speech. In this study, the researcher aims to analyse grammatical errors and speech focus on grammatical errors in presenters, which have been obtained using qualitative descriptive methods. The method of presentation is using descriptive presentation in the form of words or sentences that do not have a percentage or value in the form of numbers, where the researcher analyses according to the error class category of the data. From the results of this study, the researcher found 20 data where the data consisted of errors of auxiliary verbs and tenses.